PERBEDAAN HASIL BELAJAR SISWA ANTARA MODEL KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DENGAN GROUP INVESTIGATION (GI) PADA PEMBELAJARAN IPA DI KELAS V SDN 060934 MEDAN - Karo-karo, Demmu; Simbolon, Priska (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to determine differences in student learning outcomes between cooperative learning model type Two Stay Two Stray (TSTS) with Group Investigation (GI) model on science learning in grade V SDN 060934 Medan Academic Year 2017/2018. This research is a comparative research with experimental method. The population in the study were the students of class V consisting of 2 classes amounting to 44 people. Sampling is done by saturated sampling that is all members of the population used as a sample of 2 classes. The experiment class 1 is 22 students and the experiment 2 class is 22 students. The instrument used to know the students learning result is the test of learning result in multiple choice form. Keywords: Learning Outcomes, Two Stay Two Stray Cooperative Model, Group Investigation.